Development of the Trametes versicolor (L.) C. G. Lloyd. fungus on the wood of thermoregulated Pinus taeda L. - Santos, Luana Maria dos; Nieri, Erick Martins; Pereira, Flávia Alves; Krefta, Sandra Mara; Mata, Jéssica Batista da (Scientia Agraria Paranaensis, 2020)
The companies in the forestry sector seek highly durable wood, prioritizing the use of planted forests, and the thermal treatment is a viable alternative to provide quality to these woods. Thus, the objective of the study was to evaluate the resistance of the heat-treated Pinus taeda L wood by the attack of white rot fungus Trametes versicolor (L.) CG Lloyd. The P. taeda L. wood was deployed in joinery to obtain samples with dimensions of 30 x 15 x 2.5 cm (length x width x thickness), being treated at temperatures of 140, 160 and 180ºC. From these, 1.0 x 1.0 x 1.0 cm specimens were obtained and subjected to the fungus for six weeks. The accelerated rot test was carried out in accordance with the ASTM D2017 standard. The experiment was conducted in a completely randomized design with four treatments (T1 = 0; T2 = 140°C; T3 = 160°C and T4 = 180°C) and nine replications. The loss of mass caused by the fungus was less in heat treated wood. On the other hand, the increase in temperature did not provide greater resistance to the material. In conclusion, heat treatment has reduced the degradation caused by the white rot fungus Trametes versicolor. Heat treatment at 140°C is indicated to avoid loss of mass in P. taeda L. woods submitted to the fungus T. versicolor. All treated woods were classified as highly resistant.